MEDIA RELATIONS SEBAGAI UPAYA PEMBENTUK REPUTASI ORGANISASI - Made Dwi Adnjani (Majalah Ilmiah Sultan Agung, 2009)
Reputation is one thing important for the organization because it’s just not only about what organization do for reach positive image, but it is meaning by which an object is known and through which people describe, remember and relate to it. In practice, reputation is not static, but it’s can change every time so it’s need long time to build reputation and need a lot of things to shape the reputation.One thing that important to build reputation is media relations. The issues that made by media can give implication for reputation of the organization, so the organization  should have a good media relations.Key words: reputation, image, media relations